2D Nanomaterials: Regulating the Electrical Behaviors of 2D Inorganic Nanomaterials for Energy Applications (Small 6/2015). Issue 6 (February 2015) - Feng, Feng; Wu, Junchi; Wu, Changzheng; Xie, Yi
<x xml:space="preserve">Abstract</x> Recent advancements in regulating the electrical behavior of 2D inorganic nanomaterials for energy applications are highlighted by C. Z. Wu and co‐workers on page 654. Due to the synergetic advantages of their superior electrical conductivity and excellent reaction activity, highly conductive 2D nanomaterials open up prospects for enhancing performance in electrochemical applications towards energy conversion and storage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>